Maintaining the company and stakeholders value through restructuring in pt. Nibia - Negara Kasih, Satria; Alex Ibarat, Iriawan (The Indonesian Journal of Business Administration, 2016)
Abstract. PT. NIBIA is a vertically integrated coal mining company. The company was established in 1999 as a logging company before eventually switched their business line to coal in 2005. Since then the company continued to expand and made their mark in both domestic and international coal market. The resume of PT. NIBIA is highlighted with the possession of the stellar long term coal supply contract with PT. PLN. PT. NIBIA secured the long term contract in 2007 and started their supply in 2009. As the coal market secured by the long term contract, PT. Nibia began massive expansion by acquiring 13 mines in Jambi province and logistics transportation to ensure the readiness of both coal reserves and logistics to fulfill their supply obligation to PT. PLN. In 2012, coal industry started to deteriorate and the descend has continued until today. The significant decline in coal price has hit the PT. NIBIA profit margin. The company situation worsen by the operational issues surrounding the coal quality and delivery of the coal to its customer, PT. PLN. PT. NIBIA experience negative cashflow and has drained their working capital. As a result, PT. Nibia has forcefully ceased their operation and unable to service their debts. The purpose of this thesis is to review the business of PT. NIBIA and to provide the alternative solutions to address their business issues. The Porter's 5 Forces and SWOT analysis were utilized to analyze both internal and external factors affecting PT. NIBIA performance. Based on the business analysis, there are alternative solutions to address PT. Nibia issues namely, (i) self-insolvency proceeding (ii) new investor (iii) financial restructuring and operation overhaul. The author believes these solution could address the company issues.In this case, financial restructuring and operation overhaul have been concluded as the best suitable solution to address company issues while also protect the stakeholder's values.Â Keywords: Financial Restructuring, Operation Overhaul, Stakeholder's Value